Performance modelling of refrigerants in a vapor compression refrigeration cycle - Basharie, Siti Mariam (2005)
The simulation model based on the actual vapor compression cycle is performed in order to evaluate the performance of 14 refrigerants in terms of first law and second law efficiency. A 10% pressure drop is modelled in both the condenser and evaporator. The refrigerants that have been evaluated include R12, R22, R502, and their alternatives R134A, R401A, R401B, R402A, R402B, R404A, R407C, R4IOA, R408A, R409A, and R507. Effects of evaporating and condensing temperature on the COP, second law efficiency and irreversibility have been studied. The evaluation results show that R401A, R401B, and R409A are predicted as the best replacements for R12. R41 OA is predicted as the best alternative for R22, while R402B, R407C, and R408A are the best alternatives for R502 in terms of COP and second law efficiency. The results of actual cycle model show better predictions than that obtained with the ideal cycle model.